Research on subsidy standards for public welfare forests based on a dynamic game model—Analysis of a case in Jiangxi, China - Ding, Na; Li, Da; Zhang, Shaowen; Shi, Kankan; Chen, Wei (Frontiers in Forests and Global Change, 2023)
To understand the behavior of the main participants in public welfare forest projects, this article constructs a “forest farmers-local government-central government” dynamic game model by setting the game scope and game principles. The game payment matrix and game equilibrium solutions show that (1) expanding the value of ecological products in the forest to improve operational income will increase the participation of forest farmers; (2) the local government’s enthusiasm for leading public welfare forest projects is mainly influenced by the positive effects of planting and management costs, which provides theoretical basis for the central government to intervene in regional ecological governance; (3) when the central government leads public welfare forest projects, the enthusiasm of the local government for afforestation is positively influenced by the central government’s subsidies. Finally, based on the game equilibrium solution, the expected results of forest farmers’ operational income are calculated using the case of Jiangxi, which confirms the importance of increasing forest farmers’ operational income.